Giant Cell Tumor of the Lateral Skull Base: Diagnostic and Management Options - Gamboa, Nicholas T.; Ronna, Brenden; Gamboa, Christina T.; Palmer, Cheryl A.; Park, Min S.; Gurgel, Richard K.; Couldwell, William T.; Kalani, M. Yashar S. (Journal of Neurological Surgery Reports, 2018)
Giant cell tumor of bone (GCTB) is a rare, benign, osteolytic neoplasm that most commonly occurs in early adulthood and often involves the long bones of the body. Although GCTB largely affects the epiphyses of long bones, several reports of GCTB involvement of the cranial and facial bones exist in the literature. In addition to reviewing other reported cases of GCTBs of the lateral skull base in the literature, the authors report here on the clinical presentation, radiographic findings, and neurosurgical management of a patient found to have a GCTB of the middle and infratemporal fossae, which was treated by aggressive en bloc resection of the lateral skull base.
Keywords: giant cell tumor of bone; lateral skull base tumor; neurosurgery; osteoclastoma; radiotherapy